The Application of Tactical Games Approach to Improve Decision-Making Skills in Soccer Among Physical Education Students at Pamulang University: The Application of Tactical Games Approach to Improve Decision-Making Skills in Soccer Among Physical Education Students at Pamulang University - Aidil Putra; Acep Rohmat Nurhidayat; Saptina Retnawati (Journal of Innovative and Creativity, 2025)
Decision-making ability is a critical cognitive skill in soccer. However, conventional technique-based instruction has not been optimal in developing this aspect among Physical Education students. This study aims to analyze the effectiveness of the Tactical Games Approach (TGA) in enhancing decision-making skills among Physical Education students at Pamulang University. Method: This research employed a quasi-experimental design with a pretest-posttest non-equivalent group design. The subjects consisted of 30 students divided into two groups: the experimental group (TGA) and the control group (conventional method). The instrument used was the Game Performance Assessment Instrument (GPAI), focusing on the decision-making component. Data were analyzed using paired sample t-test, independent sample t-test, and effect size calculation (Cohen’s d). Results: The results showed that the experimental group improved their GPAI scores from 10.73 to 15.47, while the control group increased from 10.60 to 12.13. The t-test revealed a significant difference between the two groups in the posttest (p = 0.000), with an effect size of 2.59, categorized as a very large effect. Conclusion: The Tactical Games Approach was proven to be significantly effective in enhancing decision-making skills in soccer. This model is highly recommended for use in game-based sports instruction at the university level, particularly in preparing students to become both technically skilled and tactically competent.